The Role Of Proactive Behavior And Job Characteristics In Innovative Work Behavior Mediated By Transformational Leadership In Setum Tni - Erika Hendrawati; Imam Wibowo; Tatag Herbayu Latukismo (LP2M IAIN Palopo, 2026)
To find out the urgent need to understand and study empirically how proactive behavior, transformational leadership, and job characteristics can synergistically encourage innovative work behavior in order to increase the readiness and effectiveness of the duties of the TNI General Secretariat. This research uses a quantitative design approach to answer the formulation and verification of research hypotheses. This research aims to analyze the influence of exogenous variables, namely proactive behavior and job characteristics, on endogenous variables, namely innovative work behavior, through the mediating variable, namely transformational leadership. The research objects were soldiers who served at the General Secretariat of SETUM TNI at the address Jl. Cilangkap Raya No.1, RT.1/RW.3, Cilangkap, Kec. Cipayung, East Jakarta City, Special Capital Region of Jakarta 13870. The research period is from June to November 2025. The results are an urgent need to understand and study empirically how proactive behavior, transformational leadership, and work characteristics can synergistically encourage innovative work behavior in order to increase the readiness and effectiveness of the duties of the TNI General Secretariat.